No More HF: Teflon‐Assisted Ultrafast Removal of Silica to Generate High‐Surface‐Area Mesostructured Carbon for Enhanced CO2 Capture and Supercapacitor Performance. (6th January 2016) - Singh, Dheeraj Kumar; Krishna, Katla Sai; Harish, Srinivasan; Sampath, Srinivasan; Eswaramoorthy, Muthusamy
Abstract: An innovative technique to obtain high‐surface‐area mesostructured carbon (2545 m 2  g −1 ) with significant microporosity uses Teflon as the silica template removal agent. This method not only shortens synthesis time by combining silica removal and carbonization in a single step, but also assists in ultrafast removal of the template (in 10 min) with complete elimination of toxic HF usage. The obtained carbon material (JNC‐1) displays excellent CO2 capture ability (ca. 26.2 wt % at 0 °C under 0.88 bar CO2 pressure), which is twice that of CMK‐3 obtained by the HF etching method (13.0 wt %). JNC‐1 demonstrated higher H2 adsorption capacity (2.8 wt %) compared to CMK‐3 (1.2 wt %) at −196 °C under 1.0 bar H2 pressure. The bimodal pore architecture of JNC‐1 led to superior supercapacitor performance, with a specific capacitance of 292 F g −1 and 182 F g −1 at a drain rate of 1 A g −1 and 50 A g −1, respectively, in 1 m H2 SO4 compared to CMK‐3 and activated carbon.